THE ANTINOMY OF FICTIVE STATE ADMINISTRATIVE DECISION IN INDONESIAN STATUTE - Yaqub, Addinul Haq; Prawira, Dhanitya Putra; Syahroni, Muhammad Arief (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2019)
The main issue in this paper is legal uncertainty caused by the occurrence of antinomy on the Issuance of Fictive State Administration Decision by Administrative Officials. The results of the analysis show: First, the legal regulation concerning the Fictive State Administrative Decision by Administrative Officials which causes differences in paradigms and legal positions between Article 3 of UU PTUN with Article 53 of the Administration Law should be related to the type of decision based on its nature. If the Fictive State Administrative Decision is constitutive, then the decision must be based on UU PTUN, whereas if the Fictive State Administrative Decision is declarative, then the decision must be situated under the Administration Law. Second, the legal implication related to the differences in legal regulation provides a gap for Administrative Officialsto trigger unrealized legal protection to society. The difference in legal regulation also manifests legal uncertainty in the judicial process because it can cause confusion for judges to use measurement pointsin deciding state administrative disputes. Keywords: State Administrative Court; Administration Law; Legal Regulation; Constitutive; Declarative.